Shoulder Balance Following Correction Surgery for Adolescent Idiopathic Scoliosis: When Is It Achieved and Does the Type of Construct Matter?. Issue 1 (February 2022) - Moorthy, Vikaesh; Goh, Graham S.; Guo, Chang-Ming; Tan, Seang-Beng; Chen, John Li-Tat; Soh, Reuben Chee Cheong
Abstract : Study Design: This is a retrospective study. Objective: This study aims to determine (1) when shoulder rebalancing occurs after adolescent idiopathic scoliosis (AIS) correction surgery and (2) whether shoulder asymmetry was influenced by the use of pedicle screws or hooks. Summary of Background Data: Postoperative shoulder imbalance is an important outcome of AIS correction surgery as it may influence a patient's appearance and satisfaction. Materials and Methods: Seventy AIS patients undergoing AIS correction surgery at a single institution were retrospectively reviewed. Radiographic parameters were measured from anteroposterior x-rays at preoperative, immediate postoperative, 6 months postsurgery, and 12 months postsurgery. Shoulder parameters measured were: radiographic shoulder height (RSH), clavicle angle, coracoid height difference (CHD), and T1 tilt. The Cobb angle of the proximal thoracic curve, major thoracic curve, and thoracolumbar/lumbar curve. The percentage of correction was also calculated. Results: Lateral shoulder asymmetry (RSH and CHD) changed significantly from preoperative to up to 6 months postsurgery. T1 tilt, a measure of medial shoulder asymmetry, did not change significantly. Postoperatively, the hook group attained significantly better shoulder balance than the screw group in terms of RSH and CHD up to 12 months postsurgery. However, the percentage correction of the major thoracic curve was significantly greater in the screw group than the hook group (hook: 62.2±18.4% vs. screw: 76.0±16.0%, P =0.007). Conclusions: Lateral shoulder rebalancing occurs up to 6 months after surgery. While thoracic pedicle screws offer greater correction of major AIS curves, hook constructs offer better postoperative shoulder symmetry. Level of Evidence: III.